49th IEEE Conference on Decision and Control (CDC) 2010
DOI: 10.1109/cdc.2010.5717367
|View full text |Cite
|
Sign up to set email alerts
|

Reproducing slugging oscillations of a real oil well

Abstract: Abstract-This paper addresses the problem of reproducing oscillations generated by the well-known slugging phenomenon in multiphase flow. Reported investigations show how to determine the parameters of a recently proposed ordinary differential equations system, so that it captures the characteristics of actually observed slugging oscillations. A tuning procedure based on the mathematical properties of the model is presented. It is then applied to a test case consisting of a real oil well located in the North S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…The observer gain is designed so that the observer is robust to uncertainties in modeling the nonlinear functions. The structure of the high-gain observer is similar to the one used in [7]: (1), (2) and (4). For the third state equation (f 3 ), we transformed the state into top pressure which is a measurement (y = z 3 andŷ =ẑ 3 ).…”
Section: B High-gain Luenberger Observermentioning
confidence: 99%
See 2 more Smart Citations
“…The observer gain is designed so that the observer is robust to uncertainties in modeling the nonlinear functions. The structure of the high-gain observer is similar to the one used in [7]: (1), (2) and (4). For the third state equation (f 3 ), we transformed the state into top pressure which is a measurement (y = z 3 andŷ =ẑ 3 ).…”
Section: B High-gain Luenberger Observermentioning
confidence: 99%
“…One may say a observer is not high-gain, because the observer gain is K = 1 [7]. However, it depends on which unit is used for the measurement; for example there is a scaling factor of 10 3 between Pa and kPa for pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been discovered that casing-heading instability is not the only source of unstable well production, but it has been observed that it is the most significant factor for gaslifted oil-wells [2], [10]. some investigation about the gas-lift instability can be found in [3], [4], [5] and references therein, and the control of this instability can be found in [6], [7], [10]. In many practical situations at offshore platforms, the slugging problem is to handled in a manual control manner, which is definitely not cost-effective nor highly reliable.…”
Section: Introductionmentioning
confidence: 98%
“…Di Meglio et al (2010a) proposed a partially linearizing feedback controller that uses the mass of liquid in the riser for state feedback. Di Meglio et al (2010b) used a simple nonlinear Luenberger-type observer to estimate the state variable needed for the controller. However, the separation principle does not hold for nonlinear systems in general, and the closed-loop observer/controller is not 1 Corresponding author guaranteed to be stable for all conditions.…”
Section: Introductionmentioning
confidence: 99%